Molecular histology of lung cancer: From targets to treatments. Issue 4 (April 2015) - Wood, Steven L.; Pernemalm, Maria; Crosbie, Philip A.; Whetton, Anthony D.
<x xml:space="preserve">Abstract</x> Highlights Genomic sequencing has identified key lung cancer driver mutations. These can provide both prognostic/diagnostic markers as well as potential drug targets. Molecular alterations inform targeted therapy options. Future directions: ctDNA and miRNA-based assays, as well as CSC profiling have potential to provide biological insight and markers.